Molecular Diagnostic of Treponema pallidum in Blood Specimens of Donors Using Simple PCR and Real-Time PCR in Thi-qar Province, Iraq - Kamil M. Al-Jobori (Journal of Global Pharma Technology, 2018)
Syphilis is a perplexing infection; it is a complex multistage disease responsible for a range of severe clinical manifestations when untreated or as a result of treatment failure in its sole human host. The objective of current study was to diagnostic of Treponema pallidum in blood specimens of donors using molecular methods. A total of 150 samples (25 serums, 25 plasma and 100 whole blood) were used for this purpose. Samples were analyzed using simple PCR and RT-PCR by amplifying 16Sr and polA genes).During the study period, out of 150 samples of serum, plasma and whole blood collected from males and females, whole blood samples of 14 male and 1 female gave positive result for DNA extract , and and only 15 samples were positive for simple PCR and RT-PCR for the 16Sr gene . But polA gene not succeeded to amplify by simple PCR, however, succeeded to amplified 15 samples using RT-PCR. In conclusion, Blood samples, regardless of the compartment (serum, plasma or whole blood) used for testing, appear to be unsuitable for PCR analysis. However, from blood compartment whole blood was the best sample for spirochete detection of syphilis infection than from serum and plasma samples.Keywords: Blood donors, Syphilis, Treponema pallidum, 16Sr gene, polA gene, Simple PCR, RT-PCR.